Investigation of the expression and biological response of the IL-1Rrp2 receptor in human cells - Mutamba, Shilla (2012)
Dysregulated IL-1 activity has been implicated in the pathogenesis of several acute and chronic inflammatory as well as autoimmune diseases. Genomic analysis has identified additional IL-1 family members and also expanded the IL-1 receptor family. To date, there are eleven IL-1 family members and nine IL-1 receptor family members. Information regarding the biological activity and immunological role of the newer IL-1 family members is still very limited. The novel IL-1 cytokines, IL-1F6, IL-1F8 and IL-1F9 (recently renamed IL-36α, IL-36β and IL-36γ respectively) have been shown to signal via IL-1 receptor related protein 2 (IL-1Rrp2, recently renamed IL-36R). The main aims of this study were: (i) to investigate the expression of IL-1Rrp2 by human myelomonocytic and non-myelomonocytic immune cells as well as other human cells, (ii) to determine the possible function of IL-1Rrp2 and (iii) to determine the effect of IL-1Rrp2 expression on T lymphocytes. Results reported in this thesis indicate that among human myelomonocytic cells, constitutive IL-1Rrp2 expression is unique to dendritic cells (DCs). IL-1Rrp2 was expressed by monocyte- derived DCs (MDDCs) and plasmacytoid DCs (pDCs) but not by peripheral blood type 1 or type 2 myeloid DCs (mDC1 or mDC2). IL-1Rrp2 expression was regulated in response to both classical (IL-1β) and novel IL-1 cytokines (IL-1F8 and IL-1F9). Similarly to IL-1β and bacterial LPS, novel IL-1 cytokines mediated DC maturation as shown by DC phenotypic changes (e.g. upregulation of HLA-DR expression and decreased CD1a expression following culture of DCs with IL-1F8) and cytokine production. Among non-myelomonocytic cells, constitutive IL-1Rrp2 expression was observed in lamina propria tissue, T lymphocytes, NCI/ADR-RES cells and HT 29 cells. IL-1F8-matured human DCs were fully functional as they induced proliferation of IFN-γ-producing TH1 subsets. Results suggest that novel IL-1 cytokines play a role in inflammatory responses involving human DCs, with possible implications for inflammatory disease.